2022
DOI: 10.1108/ijopm-03-2021-0209
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement and management systems for dealing with strategies in uncertain ecosystems

Abstract: PurposeAlthough there is a growing research stream on Performance Measurement and Management Systems (PMMS) in Ecosystems literature, current research offers limited theoretical insights into how PMMS deal with two types of strategies in uncertain ecosystems: ecosystem-based strategy – EBS (at the focal firm level) and ecosystem strategy – ES (at the ecosystem level). This study aims at identifying how PMMS are employed to deal with different types of strategies in uncertain ecosystems.Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…More recent developments of PMM theory include Pavlov and Micheli (2022), who apply complexity theory to PMM, and Micheli and Muctor (2021), who look at how PMM can be adopted at the level of business eco-systems, which are constellations of firms coming together to achieve a shared goal. Other supporting work relevant to the case of ZDFSC includes Gomes et al (2023), who consider how PMM might operate where such eco-systems include uncertainty, pointing to the need for inter-organisational learning processes. Other relevant research (Legenvre and Hameri, 2023) includes how data sharing processes can emerge along complex supply chains.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent developments of PMM theory include Pavlov and Micheli (2022), who apply complexity theory to PMM, and Micheli and Muctor (2021), who look at how PMM can be adopted at the level of business eco-systems, which are constellations of firms coming together to achieve a shared goal. Other supporting work relevant to the case of ZDFSC includes Gomes et al (2023), who consider how PMM might operate where such eco-systems include uncertainty, pointing to the need for inter-organisational learning processes. Other relevant research (Legenvre and Hameri, 2023) includes how data sharing processes can emerge along complex supply chains.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…Similarly, research on deforestation and supply chains includes legal studies (Grabs et al , 2021) or geography (Lambin et al , 2018; Lambin and Furumo, 2023) rather than management studies. Hence, we seek to conduct theory elaboration on PMM from the perspective of ZDFSC.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…Indeed, Adner (2017) argues that the ecosystem strategy refers to how firms will pursue this alignment. Building on this, Gomes et al (2023) advocate for the existence of two types of strategy, an ecosystem-based strategy where the firm wants to guarantee its role in the ecosystem, and an ecosystem strategy where the goal is to guarantee the success of the ecosystem competing with rivals (Gomes et al, 2023). Indeed, the notion of competition within and across ecosystems is central to understanding its dynamics (e.g., Hannah and Eisenhardt, 2019;Rietveld and Schilling, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Third, there is a lack of research exploring how firms competing in the ecosystem change their innovation processes given the new strategy. The literature has shown that firms employ different strategies when dealing with ecosystems (Gomes et al, 2023;Hannah and Eisenhardt, 2019;Kretschmer et al, 2022;Rietveld et al, 2019;Rietveld et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation